The impact of market and nonmarket strategies on firm performance in Lithuania - Parnell, John Alan (Economic and business review, 2025)
This study examines the impact of market strategies (global growth, differentiation, and cost leadership) and nonmarket strategies (political engagement and social responsibility) on firm performance in Lithuania. Based on survey data from 114 managers analyzed using partial least squares structural equation (PLS-SEM) modeling, a global growth/differentiation strategy has a positive impact on performance, whereas cost leadership does not. Nonmarket strategies positively influence firm performance, with larger firms benefiting more, ostensibly due to greater resource availability and institutional influence. Firm size moderates the relationship between nonmarket strategies and perfor- mance, highlighting the importance of tailoring strategies to an organization’s specific characteristics. By focusing on firm size as a moderating factor, this study offers a nuanced understanding of how firms in Lithuania adapt strategies to align with evolving institutional frameworks and market dynamics. Managers in transitional and recently transi- tioned economies should integrate market and nonmarket strategies effectively while tailoring approaches based on organizational size.
Keywords: Central and Eastern Europe; company performance; entrepreneurship; Litva; podjetništvo; poslovanje podjetja; srednja in vzhodna Evropa